중국의 한국전쟁 동의와 참전 결정 — ‘진영론’과 ‘안전론’ 사이 — - 한상준 (중국근현대사연구, 2020)
The victory of the Chinese revolution during the civil war was a measure of the survival of China. China had to build its own New China by creating a national regime through its victory in the civil war. During this period, the direction and goal of the diplomatic line that China should pursue were clear, and the position and choice of China were clear. The Soviet Union is pursuing a unilateral policy. Strengthening the “revolutionary nature” of the Sino-Korean alliance and China's own through one-sided policies was an inevitable option for the survival of China and the success of the Chinese revolution. Following Mikoyan's visit to China in March 1949 and Liu Shaoqi's visit to the Soviet Union in late June 1949, the signing of the Small and Medium Business Alliance in February 1950 was both a process and a fruit of China's unilateral policy pursued by China. The issue of handling the Korean War, which was faced by China shortly after the establishment of New China, posed a critical question to the Chinese revolutionary and security views. The Chinese Communist Party, which led the Chinese revolution to victory, could not oppose the decision as long as North Korea and the Soviet Union reached an agreement on the outbreak of the Korean War. China, which had to focus on building a socialist system after the establishment of the central government, was forced to hesitate in the outbreak of the Korean War, which could have a huge negative impact on the economic development and national construction of new countries. I believe that the Chinese government should approach the outbreak of the Korean War separately from the Chinese government's consent to the outbreak of the Korean War. Consent to the Korean War was an inevitable choice for the Chinese, whose “inertiveness of revolution” was strong, and the decision to leave the Korean War was an active choice for the Chinese, which had to protect the safety of the fledgling socialist regime. In this respect, the Chinese security view was strongly influenced by the ‘socialist camp logic’ at the war consent stage, and the Chinese security view at the war-fighting decision stage by the ‘national safety theory’ to protect the safety of the new regime.
Keywords: 阵营論; 安全論; 戰爭同意; 出兵決定; 朝鮮戰爭; theory of camp logic; theory of safety; consent to war; dispatch decision; Korean War; 진영론; 안전론; 전쟁동의; 출병결정; 한국전쟁